ADINATONSKI FRAZEMI GOVORA KRAJA ROŽAJE (ČRNA GORA) S SEMANTIKO NIKOLI IN NIKJER - Mujević, Dženisa (Slavia Centralis, 2026)
This paper presents an analysis of adinatonic idioms (or adynatons) of the Rožaje dialect with the meanings ‘never’ and ‘nowhere’, with a focus on the formation and functioning of the adynaton as a mechanism in semantic transpositions. Our goal is to examine the productivity of the adinatonic mechanism in the above meanings, and to determine the motivational basis of adinatonic constructions. The corpus consists of 20 selected idioms. This is due to the limited scope of the paper preventing a detailed analysis of all the recorded idioms. The paper, nevertheless, contributes to a preciser theoretical definition of the adynaton and provides insight into the motivational bases of adinatonic structures.
Keywords: nowhere; never; adynaton; expressiveness; idiom; Rožaje